Cytotoxic effect of commercial Humulus lupulus L. (hop) preparations – In comparison to its metabolomic fingerprint - Mohamed A. Farag; Ludger A. Wessjohann (Journal of Advanced Research, 2013)
Hops (Humulus lupulus L. Cannabaceae) is an economically important crop, that has drawn more attention in recent years due to its potential pharmaceutical applications. Bitter acids (prenylated polyketides) and prenylflavonoids are the primary phytochemical components that account for hops resins medicinal value. We have previously reported on utilizing untargeted NMR and MS metabolomics for analysis of 13 hops cultivars, revealing for differences in α- versus β-bitter acids composition in derived resins. In this study, effect of ratios of bitter α- to β-acids in hop resins to cytotoxicity of hop resins was investigated. In vitro cell culture assays revealed that β-acids were more effective than α-acids in growth inhibition of PC3 and HT29 cancer cell lines. Nevertheless, hop resins enriched in β-acids showed comparable growth inhibition patterns to α-enriched resins and suggesting that bioactivity may not be easily predicted by metabolomics and/or gross metabolic profiling in hops.